Implementation of Semester Credit System Management in Accelerating Learning - Nurul Atika Hasibuan; Rustam Rustam (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the implementation of the Semester Credit System (SKS) management in accelerating learning at MAN 2 Model Medan. The research employs a qualitative approach with a case study design. The research subjects include the principal, vice principal for curriculum affairs, teachers, and students selected purposively. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using the interactive model of Miles and Huberman, with triangulation to ensure data validity. The findings indicate that the implementation of SKS has been carried out effectively and systematically through well-structured planning, flexible execution, and continuous evaluation. The acceleration of learning is supported by an adaptive curriculum, innovative teaching strategies, academic guidance services, as well as adequate facilities and infrastructure. Furthermore, the success of SKS implementation is influenced by managerial collaboration, teacher readiness, and students’ independence in managing their learning load. Therefore, the SKS can serve as an effective strategy to optimize students’ potential without compromising the quality of learning.